2018
DOI: 10.25105/urbanenvirotech.v1i2.2426
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Noise on Work Fatigue in an Oil and Gas Industry

Abstract: <strong>Aim:</strong> The purpose of this study is to determine the effect of noise on work fatigue at Central Processing Plant (CPP) Gundih Completed. Noise is one of the causes of fatigue in the oil and gas industry. <strong>Methodology and Result</strong>: Noise is measured using a Sound Level Meter at 45 sampling points spread across two gas processing zones at CCP Gundih in Cepu is Utility zone and Main Process zone. The noise distribution pattern based on noise level in gas proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The study found that 64.1% of the workers experienced mild work fatigue (Rahmawati & Tualeka, 2019). In the Oil and Gas Industry, it was also found that noise has a 39% effect on work fatigue at noise intensities between 85.967 dB(A) and 87.155 dB(A) (Hebrani et al, 2018).…”
Section: Lactic Acid Level Measurementmentioning
confidence: 94%
“…The study found that 64.1% of the workers experienced mild work fatigue (Rahmawati & Tualeka, 2019). In the Oil and Gas Industry, it was also found that noise has a 39% effect on work fatigue at noise intensities between 85.967 dB(A) and 87.155 dB(A) (Hebrani et al, 2018).…”
Section: Lactic Acid Level Measurementmentioning
confidence: 94%
“…Noise exposure is an essential factor causing work fatigue in chemical plant workers in France. Hebrani et al [36] concluded that noise exposure was significantly related to work fatigue in Indonesia's oil and gas industry workers.…”
Section: Noise and Heat Stress Exposure And Wrfmentioning
confidence: 99%